2022
DOI: 10.1080/07853890.2022.2092894
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of and recommendations for public health events involving brucellosis from 2006 to 2019 in China

Abstract: Brucellosis is a severe public health problem in China. However, analysis on related infection events is lacking. We performed a systematic analysis of brucellosis laboratory infection and vaccine infection events from 2006 to 2019 in China based on the published literatures. Our analysis showed that most laboratory Brucella infections in hospitals were found in Southern China. The identification and handling of suspected samples of Brucella infection without follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…In low-income countries, the current availability of next-generation sequencing technologies is woefully insufficient to meet the requirements for research carried out in those countries. The fact that there is no specific test for definitively identifying a bacterium is the primary reason for the necessary integration of multiple techniques for Brucella’ s diagnosis [ 149 , 151 , 152 ]. Although there are valid and reliable advertising and home-made molecular techniques that can ensure a high degree of accuracy and precision of results, conventional methods of culture and indirect methods of serology continue to be the primary methods of diagnosing brucellosis and following up on infections caused by Brucella species.…”
Section: Diagnostic Approaches Of Zoonotic Brucellosismentioning
confidence: 99%
“…In low-income countries, the current availability of next-generation sequencing technologies is woefully insufficient to meet the requirements for research carried out in those countries. The fact that there is no specific test for definitively identifying a bacterium is the primary reason for the necessary integration of multiple techniques for Brucella’ s diagnosis [ 149 , 151 , 152 ]. Although there are valid and reliable advertising and home-made molecular techniques that can ensure a high degree of accuracy and precision of results, conventional methods of culture and indirect methods of serology continue to be the primary methods of diagnosing brucellosis and following up on infections caused by Brucella species.…”
Section: Diagnostic Approaches Of Zoonotic Brucellosismentioning
confidence: 99%
“…Procedures involving aborting animals, aborted materials, or those in the process of parturition, as well as clinical examination, inspection, shearing, dipping, insemination, treatment, vaccination, and the disinfection and cleaning of contaminated premises pose a particularly high risk of spreading brucellosis. Therefore, the following procedures should be followed by those who are at a high risk of contracting Brucella due to their place of employment [54].…”
Section: Personal Hygienementioning
confidence: 99%
“…It is postulated that the dramatic animal husbandry growth in China was the direct cause of this situation. Additionally, an increasing tendency in number of laboratory-acquired accidental infection cases that have occurred in staffs from hospitals and universities has been noted in China, assumed to be a result of lacking a sustainable awareness regarding the risk factors associated in working with this hazardous bacterium [13]. Recently, emphasis regarding the specificity of the animal species, Brucella species, natural occurrence has been reiterated by Zhou et al who reported on Brucella canis in dogs, B. abortus in yaks, and B. suis in swine being the leading reservoirs and emerging hosts for Brucella transmission in China [14].…”
Section: Brucellosis In Chinamentioning
confidence: 99%